RETRACTED ARTICLE: Periodic Solutions of Second Order Impulsive Differential Equations at Resonance via Variational Approach - Li, Jin; Luo, Jianlin; Wang, Zaihong (Mathematical Modelling and Analysis, 2014)
View retraction statement:Retraction notice to “Periodic Solutions of Second Order Impulsive Differential Equations at Resonance via Variational Approach” [Math. Model. Anal. 19(5):664–675, 2014]